PRINSIP-PRINSIP PENGEMBANGAN KALIBRASI INSTRUMEN DALAM PENELITIAN - Roni Junaidi; Risnita; M. Syahran Jailani; Faisal Hakim Nasution (Jurnal Genta Mulia, 2024)
Research is a systematic process of investigating a phenomenon/event aimed at discovering and/or developing true knowledge. As a systematic activity, research must be carried out with a specific method known as the research method, which is a scientific approach undertaken to obtain data for a specific purpose and utility. This scientific approach must be based on the characteristics of scholarship, namely rational, empirical, and systematic. The existence of research instruments is a highly integral part and is included in the methodology component of research to conduct research activities because research instruments are tools used to collect, examine, and investigate a problem under study. A good instrument must certainly have good validity and reliability. To obtain a good instrument, besides being tested and experimented, its validity and reliability must also be calculated according to the rules of instrument preparation. In connection with this, various aspects related to research instruments will be discussed in this discussion, starting with the understanding of research instruments, types, steps of preparation, and criteria for a good instrument.